Att ta en tugga av havet: Om blå åkrar, grön ekonomi och den smarta tångens svåra resa - Fredriksson, Cecilia; Säwe, Filippa (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2020)
The marine environment has an important role to play in the change-over to a green economy where the blue fields of the sea can form new and expanded cultivation spaces. Over the recent years there has been an increasing interest for seaweed as food in Europe. In this article we follow the seaweed’s journey into the Swedish cuisine by letting it lead us to different places and actors. Seaweed are perceived as timeless and trivial, but is often presented as authentic and forward-looking. Seaweed are described as healthy and useful, but also as dirty and toxic. Seaweed is a contradictory phenomenon and it has like other natural resources the ability to organize culture and society.